Onosma ghahremanii sp. nov. (Boraginaceae), a new species from Alborz Mts., Iran - Naqinezhad, Alireza; Attar, Farideh (Phytotaxa, 2016)
Onosma ghahremanii (Boraginaceae) is described and illustrated as a new endemic species from the Alborz Mts., N Iran. The new species is related to O. gaubae, O. borragoidinum and O. microcarpum, but differs from them in indumentum type, corolla color and stamen characteristics. Some notes are also presented on the ecology, distribution, and conservation status of the new species and a distribution map is provided.